Characterising PvRBSA: an exclusive protein from Plasmodium species infecting reticulocytes - Darwin A. Moreno-Pérez; Luis A. Baquero; Diana M. Chitiva-Ardila; Manuel A. Patarroyo (Parasites & Vectors, 2017)
Abstract Background Plasmodium vivax uses multiple ligand-receptor interactions for preferential invasion of human reticulocytes. Several of these ligands have been identified by in silico approaches based on the role displayed by their orthologs in other Plasmodium species during initial adhesion or invasion. However, the cell adhesion role of proteins that are exclusive to species that specifically invade reticulocytes (as P. vivax and P. cynomolgi) has not been evaluated to date. This study aimed to characterise an antigen shared between Plasmodium species that preferentially infect reticulocytes with a focus on assessing its binding activity to target cells. Results An in silico analysis was performed using P. vivax proteome data to identify and characterise one antigen shared between P. vivax and P. cynomolgi. This led to identification of the pvrbsa gene present in the P. vivax VCG-I strain genome. This gene is transcribed in mature schizonts and encodes a protein located on the parasite surface. rPvRBSA was antigenic and capable of binding to a population of reticulocytes with a different Duffy phenotype. Interestingly, the molecule showed a higher percentage of binding to immature human reticulocytes (CD71hi). Conclusions This study describes for the first time, a molecule involved in host cell binding that is exclusive in reticulocyte-infecting Plasmodium species. This suggest that PvRBSA is an antigenic adhesin that plays a role in parasite binding to target cells.